The Sustainability of Government Deficits Old Vs. New Europe - Plocek, Tomáš; Stankov, Petar Valeriev; Potužák, Pavel; Vysoká škola ekonomická v Praze. Rektorát (2011)
This work analyses fiscal sustainability and position of old and new members of EU and offers some fiscal policy implications to deal with debt reduction in the aftermath of the current fiscal crisis in the EU. Fiscal policy of Old European countries is different from fiscal policy of the new members. Due to different historical development New European members have lower debt and lower GDP per capita. Many policymakers in New Europe tried to increase GDP of their countries by generating government deficits. On the other hand Old European countries are already having large debts and current fiscal crisis is one result of this fact. The recent fiscal crisis in Europe raised the question what is sustainable fiscal policy and how to achieve it. Sustainability of the policy can be divided into three groups: short term, medium term, and long term. In short term, fiscal policy is sustainable, when government is able to issue and sell government bonds. Otherwise it defaults. In medium term, fiscal policy is sustainable when debt to GDP ratio is constant or decreasing. Situation in long term is very similar to situation in medium term. The difference is in time. Long term fiscal policy is sustainable if debt to GDP ratio converges to some finite number. All the definitions are problematic and problem arises basically from fact that variables that are part of the definitions are volatile. Fiscal policy that might seem to be sustainable in times of economic expansion may become unsustainable even in short time. Exactly this thing happened in Ireland. Ireland shows another problem of sustainability definitions. The problem is that private debt can increase public debt and even threaten its sustainability. Many countries were saving their financial sector which was very expensive and this practice is increased the debt in those countries very fast. Probably the most important indicator of fiscal sustainability is interest rate on government bonds.
Reason is that price of the bonds is based on different risks that are in the assets. Countries with sustainable fiscal policy are paying lower interests than countries with unsustainable. This is reason why we tried to explain variation of interest rate on 10 years government bonds by empirical models. Two models were based on fixed effects panel data estimations and one model was based on ordinary least squares model. The panel data model showed that there was and still is huge difference between Old European and New European countries. Old Europe was viewed by markets as one segment which is relatively risk free. This lead to situation, that most important factor driving interest rates in Old Europe is the risk free rate on the German bonds. On the other hand, interest rates in New European countries are influenced by many more indicators. Most important indicator in New Europe is GDP growth and sustainability of foreign exchange reserves. Based on results of the model we came to conclusion that there is high chance that markets will start to differ among Old European countries and this could lead to increase of interest rates in some Old EU members, a conclusion which is to some degree being verified by the increased spreads between German government bonds on one hand, and Italian and Spanish bonds on the other hand in the first few weeks of August 2011. Our conclusions also suggest that the position of New Europe may stand similar in current situation. If it is true policymakers may try to adapt policy of New European countries to increase its sustainability and improve the key variables. The conclusions from this work bring several policy recommendations for improving the fiscal sustainability in Europe. First and probably the most important recommendation to fiscal policy is that policymakers should not underestimate the indicators of fiscal sustainability, which was a common practice in recent history. Countries with high GDP growth were generating large
Vedoucí práce: Petar Valeriev Stankov
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Rektorát, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses